2008
DOI: 10.14411/eje.2008.048
|View full text |Cite
|
Sign up to set email alerts
|

Weighty matters: Body size, diet and specialization in aphidophagous ladybird beetles (Coleoptera: Coccinellidae)

Abstract: Abstract. Aphidophagous ladybirds exhibit a broad range of body sizes. Until now this has been thought to be a function of the different prey densities that they feed at, with smaller ladybirds feeding at lower prey densities. The size of the prey species they feed on has been considered to have no relationship with ladybird body size. However, these arguments possess a limited capacity to explain observed data from the field. I here demonstrate a more realistic, complex approach incorporating both prey densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 53 publications
0
60
1
1
Order By: Relevance
“…The turning point may be represented by the concept of Sloggett (2008b) : ' body size trade -offs are the likely most important universal factor underlying dietary specialization in aphidophagous coccinellids ' . As our short explanation here will necessarily remain a simplifi cation, the reader is advised to study directly the two recent papers by Sloggett (2008a, b) , which contain many stimulating thoughts.…”
Section: Prey Size-density Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…The turning point may be represented by the concept of Sloggett (2008b) : ' body size trade -offs are the likely most important universal factor underlying dietary specialization in aphidophagous coccinellids ' . As our short explanation here will necessarily remain a simplifi cation, the reader is advised to study directly the two recent papers by Sloggett (2008a, b) , which contain many stimulating thoughts.…”
Section: Prey Size-density Hypothesismentioning
confidence: 99%
“…Alternative food will be discussed Anatis ocellata , but kicked away the small Myrrha octodecimguttata . A further size -related dilemma commented upon by Sloggett (2008b) is that of the relation between body size of aphidophagous ladybirds and aphid density and size. While Dixon ' s (2007) model considers only prey density (Fig.…”
Section: Prey Size-density Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…High metabolic specificity might be expected to lead to strong genetic trade-offs in the tolerance of different prey defensive chemicals, leading to a higher degree of prey specialisation. The limited evidence relating to prey chemistrybased trade-offs in invertebrate predators is mixed (Albuquerque et al, 1997;Sadeghi and Gilbert, 1999;Pekár et al, 2008), and in aphidophagous ladybirds such trade-offs have been suggested to be of limited importance compared with trade-offs related to prey capture, notably body size (Sloggett, 2008a, Sloggett, 2008b. Clearly additional work is required to link metabolic tolerance and the role of trade-offs in predators.…”
Section: Discussionmentioning
confidence: 99%
“…For example, large-sized coccinellids, such as Adalia species and Coccinella species, produce small eggs relative to their body size, whereas tiny-sized Stethorus species produce large eggs relative to their body size [9,11]. Differences in egg size between small and large species might be an adaptation to the size of their prey and the size of prey aggregations on host plants [11][12][13]. It may also reflect the oviposition strategies of a species (i.e., degree of synovigeny, number of ovarioles present in a species, and rate of egg maturation).…”
Section: Introductionmentioning
confidence: 99%